Celebrating Nicaea: The Idea of Creation in the Early Church and Its Relevance for a Recent Ecumenical Initiative Toward a Feast of Creation - Howles, Timothy (Theological studies, 2025)
This article argues that the idea of creation provided the early church with an integrative framework by which to contemplate nature. Rather than being understood merely as backdrop to the spiritual life, nature was taken as the site in which the drama of the divine economy was revealed. A retrieval of this stance could have value for the contemporary church. This will be explored with reference to a recent ecumenical initiative for a “Feast of Creation” across worldwide communions.